Efecto del fuego en el establecimiento de Arctostaphylos pungens Hbk., en ecosistemas templados semihúmedos de Durango, México - Márquez Linares, Marco A.; Jurado, Enrique; López González, Celia (Instituto de Ecología, A.C., 2016)
The frequency of establishment of Arctostaphylos pungens (manzanita) in three ecologically similar sites subject to different fire regimes was assessed for localities in the Sierra Madre Occidental in Durango, México. We found that manzanita seedlings got established more often within the first two years following the fire. Plants are also able to establish themselves without the stimulus of fire, though in lower numbers. Fire intensity and litter depth play an important role in the establishment of  manzanita seedlings.